Digital Transformation, Institutional Quality, and Environmental Sustainability: Evidence from SAARC Countries - Rehman, Saif ur; Gill, Abid Rashid (iRASD Journal of Economics, 2023)
The ecological changes i.e., global warming and climate change is uprising the apprehensions regarding environment degradation in the developing economies. The consequences of carbon emission and ecological deficit are not only problematic for one country but these are affecting the whole region. Therefore, this study assesses the influence of ICT-enabled digital transformation, IQ (institutional quality), energy consumption, and economic growth on the ecological footprint under the framework of EKC (Environment Kuznets Curve) in the South Asian Association for Regional Cooperation, (SAARC) economies over 1990 to 2018. Additionally, this analysis estimates the interaction term effect (ICT*IQ) on environment sustainability. We employed cross-section dependence (CD), second generation panel unit root (CIPS &CADF), and Wasteland’s cointegration econometric techniques. Further, the long and short run estimate concluded though PMG estimator. The PMG-ARDL results exhibited that ICT individual and combine impact lessen the environmental degradation. Moreover, the empirical results validate EKC hypothesis SAARC economies. But, institutional quality, economic growth (GDP) and energy consumption intensify environmental degradation by increasing the ecological footprint. The empirical estimates propose that ICT- enabled digital transformation innovation, diffusion and utilization in institutional framework can achieve the SDGs goals of environmental sustainability.